Sosialisasi Penggunaan Media Pembelajaran dalam Meningkatkan Pemahaman Membaca di Kelas Tinggi Sekolah Dasar - Aruni Salsabila; Najwa Nazhira; Naila Andini (SIGMA : Jurnal Sinergi Mengabdi, 2025)
Reading ability is a very important basic skill in basic education, especially for high school students. However, low interest and reading comprehension are problems that need to be overcome. This community service project aims to determine the process of socializing the use of learning media to improve students' reading comprehension in upper elementary school classes. The method used is Participatory Action Research (PAR). The results of the community service show that the socialization of the use of learning media, such as picture books, big books, and interactive media, has a positive impact on increasing students' motivation, interest, and reading comprehension. Therefore, selecting appropriate learning media is crucial in creating an effective and efficient reading learning process.